Effect of Ethanol Extract of Sugar Apple (Annona squamosa L.) Stem Bark on Rat SGPT and SGOT - Masykur Masykur; Nurdin; Lukman Hakim; Rosnizar; Widya Sari; Munira Ulfa; Novi Yana Sari; Ria Ceriana (Postgraduate, University of Mataram, 2023)
This study aims to compare hepatoprotector potency of the ethanol extract of sugar apple (A. squamosa) stem bark (EESSB) against the enzyme activity of SGOT and SGPT in rats induced by toxic doses of paracetamol. The method used in this study is Completely Randomized (CRD) consisting of 6 treatment groups and 3 replications. The parameters that are being observed in this study are phytochemical, antioxidant, clinical symptoms, macroscopic, SGOT and SGPT rats. Data were analyzed using Analysis of Variance (ANOVA) with a significant level of 5% with the Duncan test as a follow-up test. The clinical and macroscopic symptoms of rat liver including changes in color, surface structure and consistency as well as relative organ weight. Data were analyzed using ANOVA significant level 5% and Duncan's test as a follow-up test.Â Extracts contains alkaloid, steroid and phenolic compounds. The results showed that there was a significant difference (P <0.05) in the levels of SGOT and SGPT after giving ethanol extract of stem bark A.squamosa (EESSB). Based on the results of the study, it was concluded that all EESSB doses had the potential to reduce the levels of AST and ALT in paracetamol induced rats. The results showed that there was a significant difference (P <0.05) in the macroscopic changes in the liver based on changes in color and degree of liver damage. Relative organ weight had no significant effect (P> 0.05). The ethanol extract ofÂ A. squamosa (EESSB) stem bark has the potential to be a hepatoprotector, however a dose of 150 mg/kg BW is a more effective dose as a hepatoprotector against paracetamol.